(untitled) (Bangladesh Journal of Medicine, 2013)
Objectives: Different teaching aids are advocated in the medical colleges for delivery of lectures such as power point presentation, blackboard, transparency sheet, overhead projectors, extempore and lecture sheets .The aim of our study was to compare the more acceptable teaching methods between the students of Dhaka Medical College and Enam Medical College. Materials and Methods: Total one hundred students were selected from fourth year in each medical college. They were asked to fill in a fourteen item questionnaire about their perception of five lecture delivery methods. Questionnaire was properly explained. The results were analyzed separately to find out any differences between preferences of teaching methods in both medical colleges. Results: In DMC 50% students preferred traditional blackboard method ,25% PowerPoint presentations, 5% both blackboard and PowerPoint, 16% extempore and 4% lecture sheet .On the other hand, in EMC, 53% mentioned PowerPoint presentation as most acceptable, 38% blackboard, 5% combined blackboard and PowerPoint and 4% extempore. Some important comments were recorded which could be valuable for the medical teachers. Conclusion: The study showed that students of DMC clearly prefer traditional blackboard method rather than other teaching aids, whereas students of EMC prefer PowerPoint presentation. The study does not bring out any evidence based superiority of any lecture delivery method. It appears that any teaching aid can be appropriate and effective if the teachers are properly trained. This highlights the need for formal training in teaching technologies for good presentation and thus motivate the students. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13612 Bangladesh J Medicine 2010; 21: 60-64